Integrated Bioinformatics Analysis Exhibits Pivotal Exercise-Induced Genes and Corresponding Pathways in Malignant Melanoma - Zhu, Jun; Hao, Suyu; Zhang, Xinyue; Qiu, Jingyue; Xuan, Qin; Ye, Liping (Frontiers in Genetics, 2021)
Malignant melanoma represents a sort of neoplasm deriving from melanocytes or cells developing from melanocytes. The balance of energy and energy-associated body composition and body mass index could be altered by exercise, thereby directly affecting the microenvironment of neoplasm. Nevertheless, few studies towards the mechanism of genes induced by exercise and their pathways involved in melanoma were shown. Here, we used three separate datasets to perform comprehensive bioinformatics analysis and then screened the probable genes and pathways in the process of exercise-promoted melanoma. Totally, 1627 of differentially expressed genes (DEGs) induced by exercise were recognized. All selected genes were largely enriched in NF-kappa B, Chemokine signaling pathways and the response of immune after gene set enrichment analysis. The protein-protein interaction (PPI) network was applied to dig out DEGs and identified the most relevant and pivotal genes. The top 6 hub genes (Itgb2, Wdfy4, Itgam, Cybb, Mmp2, and Parp14) were identified, and importantly, 5 hub genes (Itgb2, Wdfy4, Itgam, Cybb and Parp14) were demonstrated to be related with weak disease-free survival (DFS) and overall survival (OS). In conclusion, our findings have demonstrated the prognostic value of exercise-induced genes and uncovered the pathways of these genes in melanoma, implying that these genes might act as melanoma’s prognostic biomarkers.